Evaluation of the boat acceleration - Kleshnev, V. (Rowing Biomechanics Newsletter, 2016)
An analysis of boat acceleration (BA) was made in RBN 2012/11, and seven criteria were derived. Reliable evaluation of the BA is quite a difficult task, because its pattern varies significantly in different boat types, stroke rates and skill levels. However, further analysis was made with the purpose to relate the BA pattern with other biomechanical variables and find its most informative criteria of the best rowing performance. In champion crews, values of the First Peak were about one SD higher than average and none of them had it absent at any stroke rate. his confirms the importance of this variable as a criterion of effective rowing technique.